Desain Primer Spesifik Vektor Dengue Aedes aegypti Berdasarkan DNA Pengkode ITS-1, 5.8S Ribosomal RNA, dan ITS-2 - Miranti, Kurnia Ayu; Wahyuni, Sri; Permana, Tutut Indria; Fatmawati, Diani; Nuryady, Moh Mirza (Jurnal Veteriner; Vol 24 No 1 (2023), 2023)
Identification of dengue hemorrhagic fever (DHF) vector species is important for vector control programs. Internal Transcribed Spacer (ITS) of DNA markers is one of the DNA markers that is generally used to identify a species. This study was aimed to obtain potential primers with specific results for Aedes aegypti mosquito species based on DNA sequences ITS-1, 5.8S Ribosomal RNA and ITS-2. This research was an in silico descriptive study using Primer3 and Primer-BLAST, as well as an in vitro confirmation stage was used the Polymerase Chain Reaction (PCR) method. The sequence of DNA data was obtained from NCBI with accession numbers GU980956.1 and ON652374.1. The results of in silico primer design obtained two pairs of potential primers, namely primer 1) Left 5’-CATTTGCTAGTCCCTCGGG-3’ Right 5’-CACCACACCACGTCTGAC-3’, and primer 2) Left 5’-CATTTGCTAGTCCCTCGGG-3’ Right 5’-CATCAACCGCGG TGTGTC- 3’. Visualization of PCR results was detected using a 1.5% agarose gel with a product size of aroind 800 bp. The conclusion of this study was that two pairs of ITS primers were obtained which had the potential to identify A. aegypti mosquitoes.